The impact of astrocyte mitochondrial ATP production on neuroprotection after stroke - Lechleiter, James (Henry Stewart Talks, 2013)
Schematic diagram of an ischemic stroke at cellular level, P2Y1-R stimulation, Photothrombosis, Pathways involved in ATP production in astrocytes, Working model of astrocyte neuroprotection, Ischemia-induced astrocyte cell swelling